2002
DOI: 10.2337/diabetes.51.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in Morbid Obesity

Abstract: Obesity is a frequent cause of insulin resistance and poses a major risk for diabetes. Abnormal fat deposition within skeletal muscle has been identified as a mechanism of obesity-associated insulin resistance. We tested the hypothesis that dietary lipid deprivation may selectively deplete intramyocellular lipids, thereby reversing insulin resistance. Whole-body insulin sensitivity (by the insulin clamp technique), intramyocellular lipids (by quantitative histochemistry on quadriceps muscle biopsies), muscle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
269
3
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(296 citation statements)
references
References 50 publications
15
269
3
9
Order By: Relevance
“…In obesity and type 2 diabetes, decreased fat metabolism and an accumulation of triacylglycerol has been observed in skeletal muscle, the major site of insulin resistance [2]. In a number of studies, but not all [3], an inverse relationship between insulin sensitivity and intramyocellular triacylglycerol storage has been found [4][5][6][7]. Consistent with this notion, an increase in NEFA concen-trations by lipid infusion leads to decreased insulin sensitivity [8] and increased intramyocellular triacylglycerol stores [2].…”
Section: Introductionmentioning
confidence: 79%
“…In obesity and type 2 diabetes, decreased fat metabolism and an accumulation of triacylglycerol has been observed in skeletal muscle, the major site of insulin resistance [2]. In a number of studies, but not all [3], an inverse relationship between insulin sensitivity and intramyocellular triacylglycerol storage has been found [4][5][6][7]. Consistent with this notion, an increase in NEFA concen-trations by lipid infusion leads to decreased insulin sensitivity [8] and increased intramyocellular triacylglycerol stores [2].…”
Section: Introductionmentioning
confidence: 79%
“…[11][12][13][14] Consistent with these findings is the inverse relation between intramyocellular lipid content and non-oxidative glucose disposal we found. Further evidence of cause and effect between intramyocellular lipid and insulin resistance came from a study by Greco and colleagues, 29 which showed that selective depletion of intramyocellular fat stores restored normal insulin sensitivity in obese adults, despite a persistent excess of total body fat mass. In our study, sex and ethnicity did not significantly affect the intramyocellular lipid content.…”
Section: Discussionmentioning
confidence: 99%
“…13 In sedentary O subjects, a moderate weight loss accompanied by an improved aerobic capacity leads to a normalization of mitochondrial oxidative capacity and insulin resistance. 14 However, when weight loss occurs in the absence of an increase in physical activity level, that is, without improvement in aerobic capacity, insulin resistance is normalized, 2,15 but muscle oxidative capacity remains unaltered. 5,16 In a previous study, a decreased muscle b-hydroxy-acyl-CoA-dehydrogenase (HAD) activity was observed in postobese (PO) subjects, 17 but it is not known whether the obesity-induced attenuation of fat oxidation and/or mitochondrial oxidative capacity is normalized after persistent long-term weight loss.…”
Section: Introductionmentioning
confidence: 99%